2014
DOI: 10.1111/ped.12450
|View full text |Cite
|
Sign up to set email alerts
|

Pelizaeus–Merzbacher disease: Cellular pathogenesis and pharmacologic therapy

Abstract: Pelizaeus-Merzbacher disease (PMD) is a rare leukodystrophy that causes severe dysmyelination in the central nervous system in infancy and early childhood. Many previous studies showed that various proteolipid protein 1 (plp1) mutations, including duplications, point mutations, and deletions, lead to oligodendrocyte dysfunction in patients with PMD. PMD onset and clinical severity range widely, depending on the type of plp1 mutation. Patients with PMD exhibit a delayed mental and physical development phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 76 publications
1
39
0
4
Order By: Relevance
“…We also recognize the importance of performing a study that examines inflammation in PMD autopsy tissue. Describing the central pathologic differences between PLP1 mutation types in humans is worthy of attention because it should lead to a more refined discussion on future therapies [55]. For example, in the PLP1 deletion patient, extensive myelin, albeit of abnormal composition, is present and is likely indicative of numerous functional oligodendrocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also recognize the importance of performing a study that examines inflammation in PMD autopsy tissue. Describing the central pathologic differences between PLP1 mutation types in humans is worthy of attention because it should lead to a more refined discussion on future therapies [55]. For example, in the PLP1 deletion patient, extensive myelin, albeit of abnormal composition, is present and is likely indicative of numerous functional oligodendrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…More than 100 point mutations have been identified within the PLP1 coding region that cause a wide spectrum of clinical abnormalities. The clinical features of PMD describing the aggressiveness of the disease and how the severity depends on the nature of the PLP1 mutation and gene expression has been well studied in animal models [22, 26, 35, 51, 55, 64, 67]. …”
Section: Introductionmentioning
confidence: 99%
“…PLP1 point mutations and duplications confer a toxic gain of function in oligodendrocytes, with consequent misfolding and aggregation of mutated PLP1 [ 46 ]. Under normal conditions, PLP1 is synthesized at the endoplasmic reticulum (ER)/Golgi apparatus, associates with lipids and is transported to myelin by vesicular transport [ 224 ]. PLP1 point mutations prevent normal trafficking of the PLP1 protein to the cytoplasmic membrane and cause its aggregation in the ER and Golgi apparatus with activation of the unfolded protein response.…”
Section: Pathology and Mechanisms Of Genetic White Matter Disorders: mentioning
confidence: 99%
“…We have reported that changes of protein properties caused by their disease mutations are associated with their disease phenotypes of oligodendrocytes [3], [4], [5], [6], [7]. We herein report that transgenic mice expressing HLD4-associated (Asp-29-to-Gly) mutant of HSPD1 exhibit a defect in myelination in brain.…”
mentioning
confidence: 71%